Effects of chronic diseases on health‐related quality of life and self‐rated health among three adult age groups. (10th December 2018) - Ge, Lixia; Ong, Reuben; Yap, Chun Wei; Heng, Bee Hoon
Abstract: Little is known about whether there is any difference in associations of chronic diseases with health‐related quality of life and self‐rated health across age groups. The purpose of the present study was to examine the associations of one specific and multiple chronic diseases with health‐related quality of life and self‐rated health (measured using the 5‐level EQ‐5D version) in three age groups: young (21–44 years), middle‐aged (45–64 years), and older adults (≥65 years). Secondary data analysis of 1932 participants in the Population Health Index Survey was performed. Linear regression results showed that different chronic diseases had a characteristic effect on health‐related quality of life and self‐rated health among different age groups. The presence of a single chronic disease was associated with lower health‐related quality of life and self‐rated health in young adults. Multi‐morbidity was consistently associated with decreased health‐related quality of life and self‐rated health in all age groups. Our findings suggest that although young adults have a lower prevalence of chronic diseases, their impacts on health‐related quality of life and self‐rated health can be as significant as that in middle‐aged and older adults.